1992
DOI: 10.1139/g92-101
|View full text |Cite
|
Sign up to set email alerts
|

X chromosome inactivation in X autosome translocation carrier cows

Abstract: The pattern of X chromosome inactivation in X autosome translocation carries in a herd of Limousin-Jersey crossbred cattle was studied using the reverse banding technique consisting of 5-bromodeoxyuridine incorporation and acridine orange staining and autoradiography on cultures of solid tissues and blood samples exposed to tritiated thymidine. The late-replicating X chromosome was noted to be the normal X in strikingly high proportions of cells in cultures of different tissues from all translocation carriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…However not all cases with a balanced X;autosome translocation exhibit complete nonrandom inactivation of the normal X chromosome [Mattei et al, 1982;Schmidt and Du Sart, 1992]. Based on late replication studies, approximately 10-15% of reported cases have an inactive der(X) in a proportion of cells with most of these cases having breakpoints in the distal regions of Xp and Xq [Basrur et al, 1992;Schmidt and Du Sart, 1992].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However not all cases with a balanced X;autosome translocation exhibit complete nonrandom inactivation of the normal X chromosome [Mattei et al, 1982;Schmidt and Du Sart, 1992]. Based on late replication studies, approximately 10-15% of reported cases have an inactive der(X) in a proportion of cells with most of these cases having breakpoints in the distal regions of Xp and Xq [Basrur et al, 1992;Schmidt and Du Sart, 1992].…”
Section: Discussionmentioning
confidence: 99%
“…Ear skin biopsies collected from two normal crossbred beef cows (with normal karyotype) and a crossbred beef cow identified as a carrier of a previously described X;autosome translocation rcp(Xp+;23q-) [Basrur et al, 1992], were used for this study. Each biopsy was chopped and the tissues were incubated in 0.5% collagenase in phosphate buffered saline (PBS) at 39 ° C for 3 h, followed by dispersal in Dulbecco's Modified Eagle's Medium (DMEM; Gibco, Grand Island, NY) containing 7% fetal bovine serum (FBS; Invitrogen Canada Inc., Burlington, ON) by repeated pipetting through a 100-l micropipette tip to make single cell suspensions.…”
Section: Cell Culture and Preparation Of Metaphase Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the characterization of some original and rare chromosomal rearrangements led to particularly interesting scientific developments (e.g. the X;autosome reciprocal translocation identified in cattle by our Canadian colleagues - Basrur et al, 1992Basrur et al, , 2001Rho et al, 2007) related to the establishment of physical gene maps and understanding of basic developmental phenomena such as X-chromosome inactivation.…”
mentioning
confidence: 99%
“…One such case is a family of cross-bred beef cattle carrying a reciprocal translocation between an X chromosome and chromosome 23, rcp(Xp+; 23q-). In this family, the translocation is maternally inherited and females invariably show non-random patterns of X inactivation, with the paternal (normal) X preferentially inactivated (Basrur et al, 1992(Basrur et al, , 2001a. Taking advantage of the morphological mark provided by this translocation to distinguish inactive from active X chromosome, an examination was carried out on the spatial distribution of a variety of histone isoforms including the histone H3, trimethylated at lysine-9 (H3K9me3) and at lysine-27 (H3K27me3), and two macro histones (macroH2A1 and macroH2A2).…”
Section: Heterochromatin Epigenetics and Chromatin Re-modelingmentioning
confidence: 99%